2010
DOI: 10.1007/s00011-010-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

IgE-dependent sensitization increases responsiveness to LPS but does not modify development of endotoxin tolerance in mast cells

Abstract: IgE-induced sensitization primes mast cells for higher response to LPS through pre-activation of NFκB transcription factor. IgE-dependent sensitization does not modify events leading to endotoxin tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Morphine effects did not involve TLR4 receptor internalization, which has been suggested as a desensitization event able to prevent LPS actions (34). Although some studies have shown that TNF is synthesized de novo after different stimuli in BMMCs (39), we have reported that IgE-dependent sensitization of BMMCs promotes the generation of a pool of TNF that is rapidly mobilized after TLR4 receptor stimulation (31). Accordingly, early LPS-induced TNF secretion in sensitized BMMCs was not sensitive to actinomycin D or brefeldin A pretreatments, but it was sensitive to morphine addition.…”
Section: Ige-sensitized Bmmcs As a Cellular Model To Study Opioid/ Tlmentioning
confidence: 73%
See 1 more Smart Citation
“…Morphine effects did not involve TLR4 receptor internalization, which has been suggested as a desensitization event able to prevent LPS actions (34). Although some studies have shown that TNF is synthesized de novo after different stimuli in BMMCs (39), we have reported that IgE-dependent sensitization of BMMCs promotes the generation of a pool of TNF that is rapidly mobilized after TLR4 receptor stimulation (31). Accordingly, early LPS-induced TNF secretion in sensitized BMMCs was not sensitive to actinomycin D or brefeldin A pretreatments, but it was sensitive to morphine addition.…”
Section: Ige-sensitized Bmmcs As a Cellular Model To Study Opioid/ Tlmentioning
confidence: 73%
“…Age-matched cultures (5-8 wk old) were used in each experiment. Routinely, BMMCs were sensitized with 100 ng/ml monoclonal anti-DNP IgE (clone SPE-7 from Sigma-Aldrich) for 18 h at 37˚C, as this treatment leads to the production of a prestored, LPS-sensitive pool of TNF (31). Cells were then washed with fresh culture medium or Tyrode's BSA buffer (135 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 1.8 mM CaCl 2 , 5.6 mM glucose, 0.5 g/l BSA, and 20 mM HEPES [pH 7.4]) and were used for experiments.…”
Section: Bmmc Culturementioning
confidence: 99%
“…Only cultures 98% positive for FcεRI receptor expression and showing a dose response of b-hexosaminidase release after IgE/Ag addition were used in the study. For each experiment, BMMCs were sensitized with 100 ng/ml a monoclonal anti-DNP IgE (clone SPE-7; SigmaAldrich) for 24 h at 37˚C, because this condition was shown to increase BMMCs' responsiveness to LPS (31,33). Routinely, after sensitization, cells were collected and resuspended in fresh culture medium or Tyrode's BSA buffer (135 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 1.8 mM CaCl 2 , 5.6 mM glucose, 0.5 g/l BSA, and 20 mM HEPES [pH 7.4]) for Western blot or immunoprecipitation experiments.…”
Section: Cellsmentioning
confidence: 99%
“…Two million IgE-sensitized WT and Fyn 2/2 BMMCs were collected and used for total RNA extraction and RT-PCR, as described (33). Briefly, total RNA was purified using TRI Reagent (Sigma-Aldrich) and suspended in 15 ml RNA secure solution (Ambion, Foster City, CA).…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation